Prevalence of Axial Spondyloarthritis Among Patients With Fibromyalgia: A Magnetic Resonance Imaging Study With Application of the Assessment of SpondyloArthritis International Society Classification Criteria. Issue 5 (May 2017) - Ablin, Jacob N.; Eshed, Iris; Berman, Mark; Aloush, Valerie; Wigler, Irena; Caspi, Dan; Likhter, Maria; Wollman, Jonathan; Paran, Daphna; Anouk, Marina; Elkayam, Ori
Abstract : Objective: To evaluate the prevalence of sacroiliitis, the radiographic hallmark of inflammatory spondyloarthropathy, among patients diagnosed with fibromyalgia syndrome (FMS), using the current Assessment of SpondyloArthritis International Society (ASAS) criteria and magnetic resonance imaging. Methods: Patients experiencing FMS (American College of Rheumatology 1990 criteria) were interviewed regarding the presence of spondyloarthritis (SpA) features and underwent HLA–B27 testing, C‐reactive protein (CRP) level measurement, and magnetic resonance imaging examinations of the sacroiliac joints. FMS severity was assessed by the Fibromyalgia Impact Questionnaire and the Short Form 36 health survey. SpA severity was assessed by the Bath Ankylosing Spondylitis Disease Activity Index. Results: Sacroiliitis was demonstrated among 8 patients (8.1%) and ASAS criteria for diagnosis of axial SpA were met in 10 patients (10.2%). Imaging changes suggestive of inflammatory involvement (e.g., erosions and subchondral sclerosis) were demonstrated in 15 patients (17%) and 22 patients (25%), respectively. The diagnosis of axial SpA was positively correlated with increased CRP level and with physical role limitation at recruitment. Conclusion: Imaging changes suggestive of axial SpA were common among patients with a diagnosis of FMS. These findings suggest that FMS may mask an underlying axial SpA, a diagnosis with important therapeutic implications. Physicians involved in the management of FMS should remain vigilant to the possibility of underlying inflammatory disorders and actively search for such comorbidities.